Sprawozdanie z projektu Wsparcie integracji cudzoziemców w województwie śląskim - Agnieszka Tambor (Postscriptum Polonistyczne)
The report concerns the principal assumptions and the first phase of the project entitled Supporting integration of foreigners in the Silesian Voivodeship, implemented thanks to co-financing obtained from the Asylum, Migration and Integration Fund. The text describes the activities undertaken by the main partners of the project, i.e. the Silesian Voivodeship Office and the School of Polish Language and Culture of the University of Silesia in Katowice. The report includes detailed information on linguis- tic and cultural education of adults and children, including a summing up of the most important content taught during Polish language classes, allowing the project partici- pants to function more easily within the Polish environment.